2012
DOI: 10.1007/s11524-012-9707-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Predictors of Adult Depression in a Community Cohort of Urban African Americans

Abstract: Depression among African Americans residing in urban communities is a complex, major public health problem; however, few studies identify early life risk factors for depression among urban African American men and women. To better inform prevention programming, this study uses data from the Woodlawn Study, a welldefined community cohort of urban African Americans followed from age 6 to 42 years, to determine depression prevalence through midlife and identify childhood and adolescent risk factors for adult depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Numerous instruments can support the measurement of stress and depression. For instance, the Composite International Diagnostic Interview diagnoses lifetime major depressive disorder (33). The Perceived Stress Scale, developed in 1983, measures the degree to which respondents appraise situations in their lives as stressful.…”
Section: Social Environmentmentioning
confidence: 99%
“…Numerous instruments can support the measurement of stress and depression. For instance, the Composite International Diagnostic Interview diagnoses lifetime major depressive disorder (33). The Perceived Stress Scale, developed in 1983, measures the degree to which respondents appraise situations in their lives as stressful.…”
Section: Social Environmentmentioning
confidence: 99%
“…Thus, the vast majority is not vulnerable even in the setting of severe medical stress. Similarly, the cumulative lifetime MDD prevalence of the general population is just 15–20% (1618). We are therefore interested in identifying any modifiable resiliency factors that may be present in over 80% of the population, particularly focusing on those faced with medical co-morbidity.…”
mentioning
confidence: 99%
“…Previous work by our research group and others found that the risk factors for depression, substance use, and their comorbidity differ somewhat by gender (Green, Fothergill, Robertson, Zebrak, Banda & Ensminger, 2013; Green, Zebrak, Fothergill, Robertson, & Ensminger, 2012; Fothergill, Ensminger, Green, & Robertson, & Juon, 2009), suggesting the importance of considering gender in the propensity score process.…”
Section: Combining Propensity Scores and Moderation Analysesmentioning
confidence: 70%
“…These variables were selected because of their relationship with depression and/or substance use or their statistical association with potential unobserved variables that may be predictive of depression and/or substance use. They are based on the social fields of the Life Course Social Fields Perspective, which has long guided the Woodlawn Study (Kellam et al, 1975), as well as previous empirical findings (e.g., Green et al, 2013; Green et al, 2012; Fothergill et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation